Number transformation design for SGCC IMS administrative switching network - Wenfeng TIAN; Lianzeng ZHAO; Lin WANG; Xiande BU (Dianxin kexue)
With the adoption of IMS technology system,the construction of IMS administrative switching network faces a series of planning research such as core network,bearer network,access network and so on.The problems of interconnection between headquarters and IMS network of provincial companies and public network,and the problem of telephone number resource allocation involves number transformation design.Based on the investigation status of State Grid administrative switching network,and the analysis of key technologies and architecture of IMS,combined with the characteristics of the electric power network,the transformation number design for IMS administrative switching network was presented,technological guidance was provided for the orderly evolution of switching network.